The Impact of Third-Party Funds, Credit Restructuring, and Non-Interest Income on Profitability - Pemayun, Anak Agung Istri Maha Iswari; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2025)
This study aims to examine the influence of Third Party Funds (TPF), credit restructuring, and non-interest income on profitability. The population consists of all banking companies listed on the Indonesian Stock Exchange, with a sample of 43 banking companies covering the period from 2020 to 2022. The data were analyzed using SPSS and multiple linear regression analysis. In this study, TPF, credit restructuring, and non-interest income are the independent variables, while profitability is the dependent variable. Financial intermediation theory and signaling theory provide the theoretical framework for explaining the findings. The analysis results indicate that TPF has a positive effect on profitability, credit restructuring has a negative effect on profitability, and non-interest income has no significant effect on profitability. Keywords: Third-Party Funds; Credit Restructuring; Non-Interest Income; Profitability; Financial Intermediation Theory; Signal Theory